Physical characterization of 2020 AV2, the first known asteroid orbiting inside Venus orbit. Issue 3 (18th June 2020) - Popescu, M; de León, J; de la Fuente Marcos, C; Vaduvescu, O; de la Fuente Marcos, R; Licandro, J; Pinter, V; Tatsumi, E; Zamora, O; Fariña, C; Curelaru, L
ABSTRACT: The first known asteroid with the orbit inside that of Venus is 2020 AV2 . This may be the largest member of a new population of small bodies with the aphelion smaller than 0.718 au, called Vatiras. The surface of 2020 AV2 is being constantly modified by the high temperature, by the strong solar wind irradiation that characterizes the innermost region of the Solar system, and by high-energy micrometeorite impacts. The study of its physical properties represents an extreme test-case for the science of near-Earth asteroids. Here, we report spectroscopic observations of 2020 AV2 in the 0.5–1.5-μm wavelength interval. These were performed with the Nordic Optical Telescope and the William Herschel Telescope. Based on the obtained spectra, we classify 2020 AV2 as a Sa-type asteroid. We estimate the diameter of this Vatira to be $1.50_{-0.65}^{+1.10}$ km by considering the average albedo of A-type and S-complex asteroids ($p_V=0.23_{-0.08}^{+0.11}$ ), and the absolute magnitude ( H  = 16.40 ± 0.78 mag). The wide spectral band around 1 μm shows the signature of an olivine-rich composition. The estimated band centre BIC  = 1.08 ± 0.02 μm corresponds to a ferroan olivine mineralogy similar to that of brachinite meteorites.